Addis Abeba, Probleme seiner Entwicklung - Engelhard, Karl (ERDKUNDE, 1970)
Addis Ababa developed in 8 decades from its origin as a katama settlement to become the first permanent capital of the Ethiopian Empire with a current population of more than 700,000. Its development can be divided into 3 periods: 1. the precolonial time to 1935, 2. the short phase of Italian colonialism, 3. the period of post-war development shaped by modern European-American urban culture. If rural Ethiopian life-styles and building forms dominated the first period, modern urban characteristics have pushed more strongly into the foreground since the Italian colonial period. Administrative functions and trade - Addis Ababa has Africa's largest market - form the basis of existence for the capital of Ethiopia. Industry, which is still unimportant, will in future contribute more strongly to the diversifica tion of the city's economic base. The turbulent population growth of the post-war period - the annual growth rate has been 6,2 % over the last 10 years - makes planned development essential. After the Italian Development Plan for Addis Ababa and the Master Plan of Sir Patrick Abercrombie (1954), the Master Plan of the French Mission for Town Planning has, since 1967, determined the course of the most recent and future de velopment. The main goals of planning are the further development of infrastructure, necessary for the further development of the city, a tidy demarcation of the various urban functions, and planned control of further growth.